Produtividade de soja em terras baixas submetida a níveis de desfolha artificial no início do florescimento - (:unkn) unknown (Universidade Federal do Pampa, 2017)
In the lowlands, the incorporation of soybeans into the rice production system can improve the physical, chemical and biological aspects of the soil, but the rainfed crops may present greater difficulties to overcome stresses when they are inserted in rice soils. Therefore, the objective of this work is to evaluate the productivity of soybean cultivated in lowland areas in relation to the level of artificial defoliation at the beginning of flowering. In the experiment, soybean plants of the cultivar BMX Potência, in stage R2, were submitted to levels of 33, 66 and 100% of artificial defoliation, besides the control with 0% of artificial defoliation, besides the control with 0%, being evaluated Total Number of Pods, LAI in R5, Thousand Grain Weight and Productivity. The variables Total Number of Pods and Productivity were statistically different according to the treatments, with a maximum reduction of 51.2 and 54.7%, respectively, and the variables LAI and Weight of Thousand Grains, despite a reduction of 35.6 and 11.7%. Presented statistical difference. The culture presented recovery capacity of LAI when defoliated in R2, but there was a great reduction in productivity.
Keywords: Pragas; Dano; Rotação de culturas; Pests; Damage; Croprotation; CNPQ::CIENCIAS AGRARIAS